Isolation and characterization of endophytic fungi associated with Ephedra alata (macroscopic and microscopic characterization) - Fatima, Zair; Lakhdar, Mebarki (Journal of Agriculture and Applied Biology, 2023)
Ephedra alata, known in Algeria as Alanda, is a medicinal plant belonging to the Ephedracea family, it looks like a shrub without leaves. This species can grow in semi-arid and desert conditions thanks to its high tolerance to water shortage. It is used in traditional medicine for its therapeutic properties, in particular to treat the bronchi, the circular system, digestive system disorders, kidneys, oedema, fever, headaches, allergies, and to relieve asthma attacks as well as bacterial and fungal infections this is due to its production of secondary metabolites with a wide range of biological activities. On the other hand, This plant represents a host that allows endophytic fungi to feed, protect and spread; in return, this plant also benefits from certain advantages of endophytes. Despite its importance, no studies on its endophytic fungi has been conducted to date. This study aimed to isolate and identify the fungal endophyte community associated with the plant Ephedra alata growing in arid environments. the harvest of the Ephedra alata plant (aerial part) was made in the region of Bechar (southwest algeria). Isolation and purification of fungal strains were carried out on PDA medium supplemented with lactic acid. The identification of the isolated strains was made on the basis of morphological and cultural criteria. Ephedra alata presents a wide diversity of fungal species with a high load. A total of twelve fungal strains were isolated and the predominant genera were Aspergillus, then Penicillium, Mucor, and unidentified structures in small percentages. The most common phylum of fungal genera identified was Ascomycota, followed by Zygomycota and small percentages of unidentified structures (SNI).